On-road measurement of NH3 emissions from gasoline and diesel passenger cars during real world driving conditions. (October 2017) - Suarez-Bertoa, Ricardo; Mendoza-Villafuerte, Pablo; Riccobono, Francesco; Vojtisek, Michal; Pechout, Martin; Perujo, Adolfo; Astorga, Covadonga
Abstract: NH3 is a precursor of PM2.5 which deteriorates urban air quality, affects human health and impacts the global radiation budget. Since vehicles are important sources of NH3 in urban areas, we have satisfactorily studied the possibility of measuring NH3 emissions from gasoline and SCR-equipped diesel light-duty vehicles during real driving on-road operation using a portable FTIR. The performance of the portable FTIR resulted to be comparable to that of a laboratory-based FTIR during a series of experiments performed in the Vehicle Emission Laboratory (VELA) using the World-harmonized Light-duty Test Cycle (WLTC). Higher on-road NH3 emission factors were obtained for the gasoline vehicle than for the diesel. High NOx emissions were measured from the diesel vehicle, indicating a low efficiency of the DeNOx system, SCR. On-road NH3 emission factors were ∼2 times lower than during the laboratory tests at 23 °C for both vehiclesNH3 emissions were not observed for the diesel vehicle during cold start operation. However, NH3 cold start emissions from the gasoline vehicle were up to 2 orders of magnitude higher than during the entire road trips, ranging from 45 to 134 mg km −1 . Cold start emissions are of paramount importance as they commonly take place in urban areas. Hence, future urban reductions in PM2.5 might need to take into consideration the introduction of NH3 emissions limits for passenger cars. Highlights: NH3 on-road emissions were measured using a portable FTIR. High NH3 emissions were observed during cold start. RDE evaluation could be applied for NH3 in the future.